Lean Ergonomics—are relevant synergies of digital human models and digital twins defining a~new emerging subdiscipline? - Stefan Brunner; Verena Knott; Klaus Bengler (Zeitschrift für Arbeitswissenschaft, 2022)
Abstract Manufacturing companies are facing new kinds of challenges. High cost and time pressure as well as the variety of product variants have added to supply chain issues due to unvorseeable major political, societal or natural events. This requires more than ever load optimization for all agents of a~socio-technical system, to enable them to operate competitively and sustainably. Digital tools offer the possibility to proactively plan and analyze diverse processes. Recent developments indicat that human-centric (DHM) and process-centric (DT) tools are diverging rather than converging. The objective of this position paper is to analyze whether the vacuum created by human-centric and process-centric tools can be filled by the new subdiscipline of Lean Ergonomics (LE). LE is defined by synergies of production ergonomics and production management. Practical Relevance : By elaborating a~methodological separation of Digital Twin (DT) and Digital Human Modeling (DHM), science and the economy shall be motivated to close the gap. Lean Ergonomics as an intersection of human-centered and system-centered engineering has the potential to incentivize companies to move towards sustainable ergonomics, as the company will directly benefit from this. Ergonomic methods and Key Performance Indicators (KPIs) at the micro level of the individual workstation enable the ergonomic and psychophysiological assessment of the human being in digital and analogue form. This is mirrored on production-organizational methods and KPIs and thereby tested for dependencies and interactions, which enable a~holistic optimization of the socio-technical system. @Produzierende Unternehmen stehen vor neuartigen Herausforderungen. Hoher Kosten- und Zeitdruck sowie die Vielfalt der Produktvarianten führen zu Problemen in den Lieferketten. Dies wird intensiviert durch unvorhersehbare politische, gesellschaftliche oder natürliche Großereignisse. Eine Belastungsoptimierung für alle Akteure eines sozio-technischen Systems ist somit unabdingbar, um wettbewerbsfähig und nachhaltig agieren zu können. Digitale Tools bieten die Möglichkeit, diverse Prozesse proaktiv zu planen und zu analysieren. Aktuelle Entwicklungen zeigen jedoch, dass sich menschorientierte (DHM) und prozess- bzw. systemorientierte (DT) Methoden eher separieren statt verbinden. Das Ziel dieses Positionspapiers ist es, zu analysieren, ob das Vakuum, das durch menschzentrierte und prozesszentrierte Vorgehensweisen entstanden ist, durch die neue Subdisziplin ,,Lean Ergonomics“ (LE) gefüllt werden kann. LE definiert sich durch Synergien von Produktionsergonomie und Produktionsmanagement. Praktische Relevanz : Durch die Ausarbeitung einer methodischen Trennung von Digital Twin (DT) und Digital Human Modeling (DHM) sollen Wissenschaft und Wirtschaft motiviert werden, die Lücke zu schließen. Lean Ergonomics als Schnittpunkt von menschzentrierten und systemzentrierten Engineering hat das Potenzial, Anreize für Unternehmen zu schaffen, sich in Richtung nachhaltiger Ergonomie zu bewegen, da Unternehmen direkt davon profitieren. Ergonomische Methoden und Kennzahlen (KPIs) auf der Mikroebene des Einzelarbeitsplatzes ermöglichen die ergonomische und psychophysiologische Beurteilung des Menschen in digitaler und analoger Form. Dies wird auf produktionsorganisatorische Methoden und KPIs gespiegelt und dabei auf Abhängigkeiten und Wechselwirkungen geprüft, die eine ganzheitliche Optimierung des sozio-technischen Systems ermöglichen.
Keywords: 330; Lean Ergonomics; Digital Twin; Digital Human Modeling; Theory of Science; Human-Centered Engineering; Digitaler Zwilling; Digitale Menschmodelle; Wissenschaftstheorie; Menschzentriertes Engineering